PENGARUH TEKNIK BATUK EFEKTIF TERHADAP PENGELUARAN SEKRET PADA PASIEN TB PARU (STUDI EKSPERIMENTAL DI POLI PARU RSUD UNIT SWADANA PARE KABUPATEN KEDIRI TAHUN 2008) - Susilowati, Susilowati; Kristiani, Dwi (Akademi Keperawatan Pamenang, 2011)
Effective cough technique is an action to clearance the airway from secretion and mucus Effective cough technique especially conducted to the patient with Tuberculosis who had problem on expenditure of airway secretion. Various means have been conducted to lessen to heaping of secretion by deep breathing technique and effective cough technique/ maneuver. Intention of this research is to know is there any influence the effective cough technique to expenditure of airway secretion at patient with lung tuberculosis in Pulmonology clinic of Pare Public Hospital (RSUD Pare) Kediri in 2008. Design of this study was pre experimental design with post test only design. Object of the study was all patient with lung tuberculosis who experienced problems in airway secretion expenditure at pulmonology clinic of RSUD Pare. Total population of the study was 38 patients. Sampling technique used was consecutive sampling and the sample size was 34 patients. Data had been collected by using observation sheet before and after conducted by effective cough technique from March,10th to March,18th 2008. Then data analyzed descriptively . Result of research indicate that there is influence of effective cough technique to expenditure of airway secretion at patient with pulmonal tuberculosis in Pulmonolical clinic of Pare Public Hospital. It Showed that result of before technique cough effective equal to 38,2% and after technique cough effective equal to 70,6% its meaning of H1 accepted there is influence of effective cough technique to expenditure of airway secretion at patient with Pulmonal tuberculosis. Based on the result of the research, it is suggested to nurse to improve in effective cough teaching to the patient with pulmonal tuberculosis to lessen the presence of airway secretion of lung tissue